ҚАРАҚАЛПАҚ ЖЫРАЎШЫЛЫҚ ӨНЕРИ ҲӘМ ШАҢҚАЙ ЖЫРАЎ ДӨРЕТИЎШИЛИГИ - Эгамкулова, Г.М. (SCIENCE and SOCIETY, 2022)
This article provides some information about the Karakalpak jiravic craft, well-known jiravs who lived and worked in Bukhara and Navoi regions. The life, work and literary heritage of Shanghai Zhirov, who lived and worked in the XIX century, are analyzed.
Keywords: jirov; jirov school; bakhshi; epic; Shankay jirov; literary heritage; improvisation